Citizens of the Global South value urban green space: an example from Iran - Sahel Azizkhani Shadisheh; Kamran Shayesteh; Michael Farmer; Gad Perry (Academia Environmental Sciences and Sustainability)
The unique social and physical structures of each city affect the quality of life of its residents. Urban green spaces (UGSs) provide many benefits for both human and nonhuman life. We investigated whether residents of Hamedan City, Iran, value UGSs and explored their specific preferences. Recognizing that urban planning decisions are often influenced by societal wishes, we hypothesized that residents would value UGSs and that willingness to pay (WTP), a measure of the significance of UGSs, would be correlated with individual socioeconomic status. We conducted a contingent valuation survey of 400 residents using the double-bounded dichotomous choice method and found that WTP was positively significantly correlated with both income and education levels. Respondents preferred green spaces distributed throughout the city and favored diverse land uses. The average WTP was $0.93 per person per month, totaling over $6.4 million annually. Principal component analysis identified four key predictors of WTP: economic status, geographic origin, gender, and aesthetic preference. Despite the average per capita monthly income in Iran being below $450, Iranians show an appreciation of UGSs, suggesting that citizens of other economically challenged countries would like to see greater investment in UGSs.